Scientific Literacy: How is it Evolved to Pre-Service Physics Teacher? - Chusni, Muhammad Minan; Zakwandi, Rizki; Hasanah, Aan; Malik, Adam; Ghazali, Adeng Muchtar; Ubaidillah, Mujib (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
Scientific literacy is the ability to use scientific knowledge, identify problems, and draw conclusions based on evidence, in order to understand and make decisions about nature and changes that occur in nature as a result of human activity. This study aims to determine the development of physics teacher candidates’ scientific literacy. This is important to prepare the physics teachers in the future. The method used was ex-post facto. The subjects of this research were all students of physics education Department of UIN Sunan Gunung Djati Bandung from the first to the last semester. The data collection used was essayed tests which contained the context of science, the content of science, the process of science, and the attitude of science. Data analysis was done qualitatively and quantitatively. Based on the results of this study, it indicates that the scientific literacy ability possessed by physics teacher candidate students experiencing a continuous development in terms of the context of science, science content, the process of science, and attitude to science. The result of this research may be applied by the Physics Department to make a decision or rule on how to improve the physics student’ literacy level